Defensive Medicine in Family Physicians - Kolcu, Giray; Özceylan, Gökmen (Progress in Nutrition, 2021)
Study Objectives: In this study, it is aimed to evaluate the attitudes of family physicians regarding defensive medicine. Methods: The study was designed as a cross-sectional study. In the study defensive medicine attitude scale is used. Results: 196 family physicians participated in the study. Scale raw scores average was calculated as 40.55 ± 8.30. According to total scores, 4.6% (n: 9) low, 55.6% (n: 109) medium, and 39.8% (n:78) applied high levels of defensive medicine. When the defensive medicine attitude scale score was evaluated, a statistically significant relationship was found between the participants with high defensive medicine attitude level and those who think that malpractice case will be opened in the future (p: 0.001). Conclusion: As a result the knowledge level of family physicians on the concept of defensive medicine is not enough.  Increasing the knowledge level of family physicians on the concept of defensive medicine will contribute to patient safety and will decrease the financial burden on healthcare service by decreasing the fear of being sued.